Evaluating the socio-economic drivers of household adoption of biodigester systems for domestic energy in rural Colombia - Gómez Montoya, Juan Pablo (2025)
This study examines the socio-economic factors influencing rural households in Colombia to adopt biogas technologies, emphasizing their role in promoting sustainable development and environmental commitment. The research investigates social factors such as technology perception, capacity building, and reliance on technology. Economic factors like initial investment, operating and maintenance costs, energy savings, return on investment, by-product revenue, government incentives, alternative solution costs, financial risks, and market demand are also considered. Despite the socio-economic benefits of biodigesters, barriers such as training deficiencies, regulatory issues, and sustainability challenges delay their widespread adoption. Concerns about operational reliability, costs, and maintenance further slow their acceptance. The research presents an economic model with a viability score based on economic variables correlated with regional GDP to evaluate the capacity of Colombian regions to support biodigester technology. Government support iarestrategic regions with abundant biomass and favourable economic conditions is highlighted as fundamental for promoting biogas technology in rural Colombia.